Necroptosis-related lncRNAs: establishment of a gene module and distinction between the cold and hot tumors in glioma - Cao, Kangxi; Su, Fengbo; Shan, Xuchun; Jiang, Xingyu; Ni, Zhaohui; Chen, Yan (Frontiers in Oncology, 2023)
Background: Gliomas are the most common primary tumors of the central nervous system and portend a poor prognosis. The efficacy of emerging and promising immunotherapies varies significantly among individuals. Distinction and transformation of cold and hot tumors may improve the antitumor efficacy of immunotherapy. Methods and Results: In this study, we constructed a necroptosis-related lncRNA signature based on public databases. The association of this signature with survival was assessed using the Cox regression, Kaplan-Meier survival analysis, and nomogram, external validation was also conducted in another public database. Furthermore, we performed gene set enrichment analysis (GSEA), immune checkpoint and tumor microenvironment analysis, and in vitro qRT-PCR validation. Finally, we clustered all samples into 2 clusters based on the expression of model lncRNAs and identified cluster 1 as cold tumors with fewer infiltrating T cells. Conclusions: Identifying cold and hot tumors by necroptosis-related lncRNAs can help available immunotherapeutic strategies to achieve efficacy in the precise treatment of individuals. Prior treatment failure can be overcome by targeting necroptosis-related lncRNAs.